Effect of Application of Sago Dregs and Rice Straw Biochar on Growth and Yield of Soybean (Glycine max L.) in Inceptisol - Wambrauw, Sopia Fransina; Islami, Titiek; Sumarni, Titin (Agro Bali : Agricultural Journal, 2024)
This research was conducted to determine the effect of giving sago dregs and rice straw biochar on growth and yield and to determine the correct dose of biochar for use in inceptisol soil. The research was conducted at the Experimental Garden of the Research Institute for Various Nut and Tuber Crops (BALITKABI) IP2TP Jambegede, Jl. Agriculture, No.6 Kemiri Village, Kepanjen District, Malang Regency – East Java. The design used was a Randomized Block Design (RBD), which consisted of 6 treatments and was repeated four times. There are 6 treatments, namely: P0 = without biochar; P1 = 100% rice straw biochar; P 2 = sago dregs biochar 100%; p 3 = sago pulp biochar 75% + rice straw biochar 25%; p 4 = sago pulp biochar 50% + rice straw biochar 50%; p 5 = sago pulp biochar 25% + rice straw biochar 75%. Observations included plant height, number of leaves, leaf area, seed weight per plant, and weight of 100 seeds. Data were analyzed using a variance test (Anova) by MS Excel. The results of this research show that the administration of sago dregs biochar and rice straw has a significant effect on yield and growth, where treatment (P3) with a mixture or combination of 75% sago dregs + 25% rice straw biochar, gave the best response compared to other treatments, with results reached 1.64 t.ha-1. Thus, a mixture or combination of 75% sago dregs biochar + 25% rice straw biochar can be used in Inceptisol.